PENGARUH CHATGPT DALAM PROSES PEMBELAJARAN MAHASISWA ILMU KOMUNIKASI DI UNIVERSITAS ESA UNGGUL TANGERANG - Ariel Yoga Praditya (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims to examine the impact and potential of using ChatGPT in Communication Science education. The research employs a qualitative approach to understand and describe the phenomena being studied, allowing for objective data collection. The researcher involved 10 students from the Faculty of Social Sciences at Esa Unggul University who had used ChatGPT as participants in interviews. The findings reveal that ChatGPT is frequently utilized by students to assist in understanding learning materials, developing ideas, and completing assignments. However, alongside its benefits, concerns arise regarding the accuracy of ChatGPT's responses, the lack of information variety, and the risk of dependency, which could reduce students' critical thinking and independent research skills. This study is expected to encourage students to actively contribute to the development of policies and practices for using artificial intelligence (AI) technology in higher education in Indonesia, particularly in the field of Communication Science.